Investigation of biomarkers alterations after an acute tissue trauma in human trapezius muscle, using microdialysis - Sørensen, Line Bay (Sci Rep, 2018)
Alterations in muscle milieu are suggested as important activity of peripheral drive in patients with chronic musculoskeletal pain (CMP). Microdialysis (MD) has been used in monitoring altered metabolic response pattern in muscles. However, the insertion of MD probe causes a local tissue trauma. Whether and how metabolites in trapezius muscle are affected by acute tissue trauma is unknown. Hence, this study investigated the metabolic response and nociceptive reaction of the tissue following MD probe insertion in patients with CMP and healthy individuals. Fifty-nine patients and forty pain-free volunteers were recruited. Pressure pain thresholds (PPTs) were obtained at the trapezius and tibialis muscles. Pain questionnaires determined the levels of pain related aspects. MD (20 kDa cut-off) was performed in the trapezius and samples were collected within 40 min. Interstitial concentration of the metabolites was analyzed by a two-way-mixed-ANOVA. The metabolic response pattern changed over time and alterations in the level of metabolites could be seen in both CMP and healthy controls. Pain questionnaires and pain intensities manifested clinical aspects of pain closely to what CMP patients describe. Analyzing metabolites due to acute tissue trauma by aid of MD may be a useful model to investigate altered metabolic response effect in CMP.